3D PRINTING OF PHARMACEUTICALS – LEADING TREND IN PHARMACEUTICAL INDUSTRY AND FUTURE PERSPECTIVES - NANDI, SHANKHADIP (Asian Journal of Pharmaceutical and Clinical Research, 2020)
3D printing technology is a rapid prototyping process based on computer-aided design software that is proficient to construct solid objects with various geometrics by depositing numerous layers in a sequence. The major advantages of three-dimensional printing (3DP) technology over the traditional manufacturing of pharmaceuticals include the customization of medications with individually adjusted doses, on-demand tailored manufacturing, unprecedented flexibility in the design, manufacturing of complex and sophisticated solid dosage forms, and economic benefits. Recently, many researchers have been invested their efforts in applying 3DP technology to the pharmaceutical development of drug products and different drug delivery systems. Selective laser sintering, fused deposition modeling, semi-solid extrusion, stereolithography, etc., are the multiple 3DP technologies that can be established in several customized and programmable medicines. Sublingual, orodispersible, and fast-dissolving drug delivery formulations by 3DP technology have been already manufactured. Controlled-release formulations with different characteristics, doughnut-shaped multi-layered tablets with linear release kinetics, and drug-loaded tablets with modified-release characteristics are recently fabricated using 3DP. However, few 3DP methods produce uneven shapes of dosage forms and comparatively porous structures. Cost of transition, adaptation to the existing facility, achieving regulatory approval, etc., are the present challenges that can restrict the extensive application of 3DP technology to pharmaceutical products. Intense research work for modifying the 3DP methods is simultaneously sustained for by-passing the flaws and current limitations of this technology. 3DP technology can act as a convenient and potential tool for the pharmaceutical industry which will set a revolutionary manufacturing style in the near future to facilitate patient-centered health care.